Human papillomavirus vaccine delivery in Mozambique: identification of implementation performance drivers using the Consolidated Framework for Implementation Research (CFIR) - Caroline Soi; Sarah Gimbel; Baltazar Chilundo; Vasco Muchanga; Luisa Matsinhe; Kenneth Sherr (Implementation Science, 2018)
Abstract Background Since 2012 Gavi, the Vaccine Alliance has provided financial support for HPV vaccine introduction in low- and middle-income countries (LMICs); however, funding has been contingent on establishing a demonstration project prior to national scale-up, in order to gauge effectiveness of delivery models. Although by 2016, most beneficiary countries had completed demonstration projects, few have scaled up delivery nationwide. An important barrier was the dearth of published, country-specific implementation recommendations. We employed the Consolidated Framework for Implementation Research (CFIR) as a lens to identify drivers of heterogeneous (dissimilar) implementation performance during Mozambique’s 2-year demonstration project. Mozambique presents a compelling example as the country conducted demonstration projects in three different districts with extremely different economic resources and sociocultural practices. Methods A post implementation interpretive evaluation was undertaken. Forty key informant interviews were conducted with district and health facility immunization staff, Ministry of Education managers, and teachers across the three demonstration districts, central level informants from MOH, research institutes, and immunization program partners. We compared valence and strength ratings of CFIR constructs, across diverse implementation sites, so as to explain drivers and barriers to implementation success. Two researchers coded separately, and subsequent content analysis followed pre-defined CFIR construct themes. Results Eighteen constructs emerged from informants’ responses as implementation influencers. Adaptability was identified as an important construct because delivery modalities needed to meet differing levels of girls’ school attendance. Expanding outside of school-based delivery was needed in the low-performing district, making the vaccine delivery process more complex. Available resources varied across the three sites, with one site receiving direct Gavi support, while others received primarily state-based support. These latter sites reported considerably more implementation bottlenecks, in part related to weaker infrastructural characteristics and insufficient organizational incentives. Health workers’ beliefs in importance of vaccines and an organizational culture of making personal sacrifice for immunization program activities drove implementation performance. Advocacy and social mobilization through the right opinion leaders and champions generated higher demand. Conclusion HPV vaccination presents a pertinent opportunity for the prevention of cervical cancer in Mozambique, sub-Saharan Africa, and other LMICs. However, important barriers to broad-scale implementation exist. We recommend the development of local and global strategies to overcome barriers and facilitate its expanded utilization.